Clontuskert Augustinian Priory, cloister, base - O'Donovan, Danielle (My University, 2008)
Base of reconstructed cloister, from top down moulding comprises: roll, bell, roll, roll, bell, plinth with quirks. The middle element here looks rather like the double rolls of an English Perpendicular base.
Cloister
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Cloisters (Architecture); Late Medieval; roll moldings; plinth